1996
DOI: 10.1172/jci118383
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cyclin A gene expression by homocysteine in vascular smooth muscle cells.

Abstract: Homocysteine is an important and independent risk factor for arteriosclerosis. We showed previously that homocysteine stimulates vascular smooth muscle cell proliferation, a hallmark of arteriosclerosis. We show here that homocysteine and serum increased DNA synthesis synergistically in both human and rat aortic smooth muscle cells (RASMCs). Treatment of quiescent RASMCs with 1 mM homocysteine or 2% calf serum for 36 h increased cyclin A mRNA levels by 8-and 14-fold, respectively, whereas homocysteine plus ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(107 citation statements)
references
References 35 publications
8
94
0
5
Order By: Relevance
“…Taha et al (31) suggested that Hcy induces SMC growth by a hydrogen peroxideindependent pathway, and that the effects of Hcy may combine with the known initiating events produced by oxidative stress to accelerate the progression of atherosclerosis. Tsai et al (32) showed that Hcy and serum increased DNA synthesis synergistically in both human and rat aortic SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Taha et al (31) suggested that Hcy induces SMC growth by a hydrogen peroxideindependent pathway, and that the effects of Hcy may combine with the known initiating events produced by oxidative stress to accelerate the progression of atherosclerosis. Tsai et al (32) showed that Hcy and serum increased DNA synthesis synergistically in both human and rat aortic SMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this attack, which might be caused by homocysteinylation of the vascular wall proteins by homocysteine and/or its oxidized products (homocysteic acid, homocysteine sulfinic acid, and homocysteine thiolactone), in vitro and in vivo work suggests that reduced homocysteine can inhibit endothelial cell turn-over (Wang et al, 1997) and promote smooth muscle cell proliferation (Lubec et al, 1996b;Majors et al, 1997;Tsai et al, 1994Tsai et al, , 1996. Wang et al (1997) reported that low concentrations of homocysteine (10 to 50 mol/L) specifically inhibit the growth of endothelial cells.…”
Section: Hyperhomocysteinemia-mediated Oxidant Stress Through Imbalanmentioning
confidence: 99%
“…Specifically, cyclin D1 and cyclin A induced by growth factors or serum function as growth regulators during the early G 1 phase and S and G 2 /M phase of the cell cycle respectively (Tsai, 1996). Therefore, the interactions of homocysteine and growth factors or serum induce the replication of vascular smooth muscle cells lining the blood vessels and facilitate the mechanism for homocysteine-induced atherosclerosis (Tsai et al 1994;Tsai, 1996).…”
Section: Homocysteine and Smooth Musclementioning
confidence: 99%